PICES Press, Vol. 21, No. 2, Summer 2013 - North Pacific Marine Science Organization (PICES) (North Pacific Marine Science Organization (PICES), 2013)
•The 2013 Inter-sessional Science Board Meeting: A Note from the Science Board Chairman (pp. 1-4)•ICES/PICES Workshop on Global Assessment of the Implications of Climate Change on the Spatial Distribution of Fish and Fisheries (pp. 5-8)•PICES participates in a Convention on Biological Diversity Regional Workshop (pp. 9-11)•Social and Economic Indicators for Status and Change within North Pacific Ecosystems (pp. 12-13)•The Fourth International Jellyfish Bloom Symposium (pp. 14-15)•Workshop on Radionuclide Science and Environmental Quality in the North Pacific (pp. 16-17)•PICES-MAFF Project on Marine Ecosystem Health and Human Well-Being: Indonesia Workshop (pp. 18-19)•Socioeconomic Indicators for United States Fisheries and Fishing Communities (pp. 20-23)•Harmful Algal Blooms in a Changing World (pp. 24-25, 27)•Enhancing Scientific Cooperation between PICES and NPAFC (pp. 26-27)•Workshop on Marine Biodiversity Conservation and Marine Protected Areas in the Northwest Pacific (pp. 28-29)•The State of the Western North Pacific in the Second Half of 2012 (pp. 30-31)•Stuck in Neutral in the Northeast Pacific Ocean (pp. 32-33)•The Bering Sea: Current Status and Recent Trends (pp. 34-36)•For your Bookshelf (p. 37)•Howard Freeland takes home Canadian awards (p. 38) ISSN: 1195-2512